Core Binding Factor Beta Plays a Critical Role by Facilitating the Assembly of the Vif-Cullin 5 E3 Ubiquitin Ligase - Fribourgh, Jennifer L. (American Society for Microbiology, 2014)
The HIV-1 virion infectivity factor (Vif) targets the cellular cytidine deaminases APOBEC3G (A3G) and APOBEC3F (A3F) for degradation via the host ubiquitin-proteasome pathway. Vif recruits a cellular E3 ubiquitin ligase to polyubiquitinate A3G/F. The activity of Vif critically depends on the cellular core binding factor beta (CBFβ). In this study, we investigated the Vif-CBFβ interaction and the role of CBFβ in the E3 ligase assembly. Vif-CBFβ interaction requires an extensive region of Vif spanning most of its amino terminus and zinc finger region, and cullin 5 (Cul5) binding enhances the stability of the Vif-CBFβ interaction. Our results further demonstrate that CBFβ plays a critical role in facilitating Cul5 binding to the Vif/elongin B/elongin C complex. Vif, with or without bound substrate, is unable to bind Cul5 in the absence of CBFβ. These studies support the notion that CBFβ serves as a molecular chaperone to facilitate Vif-E3 ligase assembly. IMPORTANCE The host antiviral restriction factors A3G/F inhibit viral replication. The HIV-1 protein Vif targets A3G/F for degradation. This immune evasion activity of Vif is dependent on the cellular factor CBFβ. Multiple regions of Vif are known to be important for Vif function, but the mechanisms are unclear. The studies described here provide important information about the Vif-CBFβ interaction interface and the function of CBFβ in E3 ligase assembly. In particular, our comprehensive Vif-CBFβ interface mapping results help to delineate the role of various Vif regions, determining if they are important for binding CBFβ or A3G/F. Furthermore, our studies reveal an important potential mechanism of CBFβ that has not been shown before. Our results suggest that CBFβ may serve as a molecular chaperone to enable Vif to adopt an appropriate conformation for interaction with the Cul5-based E3 ligase. This study advances our understanding of how CBFβ facilitates the Vif-mediated degradation of APOBEC3 proteins.